Pembudidayaan Tanaman Apotek Hidup di Kantor Desa Blang Krueng Aceh Besar - Cicin Sintaria Utami; Nurhayati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
A living pharmacy is the use of part of a plot of land to be planted with medicinal plants and daily necessities. The cultivation of living pharmacy plants using empty land in the yard is a positive activity. There are various types of living pharmacy plants that can be cultivated and have various benefits such as being an alternative to herbal medicine, moving land that looks arid, and becoming a spice in everyday cooking. The types of living pharmacy plants include turmeric, ginger, galangal, kencur, ginger, and lemongrass. Based on the usefulness of a living pharmacy for the community, the planting of living pharmacy plants is carried out on the empty land in the Blang Krueng village office yard as an effort to provide an overview of the easy planting process and increase people's insight about the benefits of a living pharmacy. Keywords: Living Pharmacy, Plants, Vacant Land.